Two-stage surgical treatment of subarachnoid and paryhymatous blood effects with the use of endovascular embolization of damaged aneurysm - Polkovnikov, Oleksii; Kutovoy, Igor (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2019)
Introduction. Aneurysmal subarachnoid hemorrhage (SAH) is complicated by concomitant intracerebral hemorrhage (IUD) with a frequency of 4% to 42.5%. More than 80% of patients die in conservative therapy, and when removing only hematomas without occlusion of an aneurysm, the mortality rate reaches 75%. Objectives. The aim of the study was the optimization of treatment of aneurysmatic subarachnoid haemorrhage complicated by the formation of intracerebral hematoma. Materials and methods. The analysis of the results of surgical treatment of 101 patients in the acute period of cerebral aneurysm rupture was performed. The first group of observations in which the surgical treatment was limited to endovascular occlusion of cerebral aneurysms. In the second group of observations, multi-stage surgical treatment was performed - endovascular embolization of cerebral aneurysm with subsequent removal of parenchymal hematoma for 24–48 hours. Results. In most cases, surgical treatment was limited to endovascular embolization of the ruptured aneurysm. In 3 observations, multistage surgical treatment was performed - endovascular embolization of cerebral aneurysm with subsequent removal of intracerebral hematoma. In two cases, positive dynamics with a regression of neurological deficits in the postoperative period was noted. In one observation, partial regression of motor deficit. Conclusions. Two - stage surgical treatment of subarachnoid haemorrhage with intracerebral hematoma the use of endovascular embolization of the ruptured aneurysm and subsequent evacuation of hematoma is effective and can be used in cases where there is a technical possibility of occlusion of the aneurysm s and the compensated state of the patient.